Earnings management and accounting performance of new firms listings: evidence from the Vietnamese stock market - Anh Huu Nguyen; Chi Thi Duong (Cogent Business & Management, 2022)
The purpose of this article is to investigate the phenomenon of earnings management and its impact on accounting performance at the time of the listing event. The analysis is based on a sample of 189 firms listing their securities on the Ho Chi Minh, Vietnam stock exchange for the period of 2009 to 2017. Four cross-sectional models were adopted for this study to estimate earnings management with two models based on total accruals and two models based on current accruals. The article first provides evidence that Vietnamese firms aggressively manipulate their earnings upward in the year before listing in an attempt to meet listing requirements when adopting current accruals models, but not when earnings management was measured by total discretionary accruals. Additionally, firms exhibit a significant decline in accounting performance (measured by ROE and ROA) for two consecutive years after listing. Consistent with our expectations, earnings management (measured by discretionary current accruals) in the pre-listing year are negatively related to poor accounting performance for two years after listing but not in the listing year. This study also provides an additional robustness check on the results with respect to handling outliers. The findings from this research make a number of contributions to the earnings management literature and are relevant for investors, policymakers, and firms.
Keywords: L25; M41; 650; Accounting performance; discretionary current accruals; earnings management; new listings; Vietnamese stock market